The Role of the Bali’s Korean Pop Fandom in Supporting South Korea’s Soft Power - Putu Ratih Kumala Dewi (Universitas Diponegoro, 2021)
K-Pop has become a global phenomenon embarked by the Korean government as part of its cultural diplomacy, with the help of other elements such as K-Pop Fans. The existence of K-Pop is inseparable from its loyal fan community called fandom. This research thus aims to explore the phenomenon of K-pop fandom around the world and the role it plays in the globalization of K-Pop. The objective of this research is to examine the role of K-Pop fandom as a non-state actor in South Korea’s public diplomacy and in supporting the dissemination of K-Pop as a global culture. This research applies qualitative descriptive method where primary data are obtained through interviews with members of K-Pop fandom in Bali. In addition, secondary data will also be obtained through studying past literatures. Furthermore, this research utilizes the concept of public diplomacy and soft power. In the end, this research found that, K-Pop fandom, plays its role as a referee while the public is the receivers. As a ‘referee’, not only they act as a consumer of K-Pop, but K-Pop fandom also serve as a distributor and producer. The finding of this study is beneficial to understand the significance of non-state actors in the dissemination of ‘pop’ culture as part of public diplomacy as seen in South Korea.